Chiropractic & Manual Therapies - Walker, Bruce F.; French, Simon
Chiropractic & Manual Therapies publishes manuscripts on all aspects of evidence-based information that is clinically relevant to chiropractors, manual therapists and related health care professionals. Chiropractic & Manual Therapies is an open access journal that aims to provide chiropractors, manual therapists and related health professionals with clinically relevant, evidence-based information. Chiropractic and other manual therapies share a relatively broad diagnostic practice and treatment scope, emphasizing the structure and function of the body's musculoskeletal framework (especially the spine). The practices of chiropractic and manual therapies are closely associated with treatments including manipulation, which is a key intervention. The range of services provided can also include massage, mobilisation, physical therapies, dry needling, lifestyle and dietary counselling, plus a variety of other associated therapeutic and rehabilitation approaches. Chiropractic & Manual Therapies continues to serve as a critical resource in this field, and as an open access publication, is more readily available to practitioners, researchers and clinicians worldwide.